2021
DOI: 10.1007/s13691-021-00515-w
|View full text |Cite|
|
Sign up to set email alerts
|

Vitiligo and tumor response in a patient with amelanotic melanoma undergoing nivolumab treatment

Abstract: Vitiligo, an acquired depigmenting disorder of the skin that reacts against normal melanocytes, sometimes occurs as an immune-related adverse event in the treatment of melanoma with immune checkpoint inhibitors. It has been known that the occurrence of vitiligo is associated with a favorable therapeutic response in patients with melanoma, but it is not yet clear whether the association also applies to amelanotic melanoma, a minor subtype of melanoma with little or no melanin pigmentation. We report a patient w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Systemic therapy with immune checkpoint inhibitors and targeted therapies may be required. Nivolumab and ipilimumab have shown promising results in the treatment of AMM [ 10 ]. However, other studies have reported that postoperative radiotherapy only had beneficial effects on the ameliorating locoregional spread and no data to date suggested an overall survival benefit [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Systemic therapy with immune checkpoint inhibitors and targeted therapies may be required. Nivolumab and ipilimumab have shown promising results in the treatment of AMM [ 10 ]. However, other studies have reported that postoperative radiotherapy only had beneficial effects on the ameliorating locoregional spread and no data to date suggested an overall survival benefit [ 11 ].…”
Section: Discussionmentioning
confidence: 99%